(untitled) (Bangladesh Journal of Botany, 2014)
The leaf extracts from four medicinal plants viz., Azadirachta indica A. Juss., Tectona grandis L.f., Dalbergia sissoo Roxb. and Eucalyptus tereticornis J.E. Smith were evaluated using Pisum sativum (Linn.) reduced mitotic index in a dose-dependent manner. The percentage of increasing abnormal mitotic plates was also concentration and time dependent. Commonly observed abnormalities were c-mitosis, laggard, bridges, stickiness, precocious separation, vagrant and fragments. The results indicate that commonly used aqueous leaf extracts of above plants has significant mutagenic action on plant model P. sativum var. Arikil. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19760 Bangladesh J. Bot. 43(1): 107-111, 2014 (June)